2021
DOI: 10.1186/s12970-021-00416-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of six weeks 1000 mg/day vitamin C supplementation and healthy training in elderly women on genes expression associated with the immune response - a randomized controlled trial

Abstract: Background In this study, we investigated the effects of supplementation and exercise on the expression of genes associated with inflammation like CCL2, CRP, IL1, IL6, IL10 mRNA in elderly women. Methods Twenty four participants divided randomly into two groups were subjected to 6 weeks of the same health training program (three times per week). SUP group (supplemented, n = 12, mean age 72.8 ± 5.26 years and mean body mass 68.1 ± 8.3 kg) received 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The authors emphasized the selective influence of vitamin C on cytokines [ 37 ]. On the contrary, Żychowska et al [ 39 ] investigated the effects of supplementation and physical exercise on the expression of genes related to immune response, such as CCL2 , CRP , IL-1 ; IL-6 and IL-10 in women. The clear tendency of a decrease in IL-6 and an increase in IL-10 mRNA was observed in leukocytes from the training women supplemented for 6 weeks with 1000 mg of vitamin C as referenced to the control group receiving placebo.…”
Section: Vitamin C and Its Mechanisms Of Immunomodulationmentioning
confidence: 99%
“…The authors emphasized the selective influence of vitamin C on cytokines [ 37 ]. On the contrary, Żychowska et al [ 39 ] investigated the effects of supplementation and physical exercise on the expression of genes related to immune response, such as CCL2 , CRP , IL-1 ; IL-6 and IL-10 in women. The clear tendency of a decrease in IL-6 and an increase in IL-10 mRNA was observed in leukocytes from the training women supplemented for 6 weeks with 1000 mg of vitamin C as referenced to the control group receiving placebo.…”
Section: Vitamin C and Its Mechanisms Of Immunomodulationmentioning
confidence: 99%
“…Antioxidants, including vitamin C and NAC, significantly reduce CRP concentrations and other inflammatory markers and cytokines, which are key adaptive changes to training, by inhibiting nuclear factor kappa B. 5357 Zinc counteracts insulin resistance, reduces CRP concentrations, and protects against cardiovascular disease. Zinc produces these effects because it is an essential trace element in many enzymes, particularly the antioxidant superoxide dismutase, and is involved in insulin homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of supplemental vitamin C to enhance immune function has been investigated in adults, including older adults, in several studies. One study reported that 6 wk of vitamin C supplementation (1000 mg/d) in elderly women (mean age: 72.8 y) resulted in no significant changes in leukocyte expression of genes encoding the proinflammatory markers IL-1, IL-6, and CRP or the anti-inflammatory marker IL-10 ( 94 ). However, a clear trend of decreasing IL-6 and increasing in IL-10 mRNA was observed ( 94 ).…”
Section: Micronutrients Immunity and Infection With An Emphasis On Ol...mentioning
confidence: 99%
“…One study reported that 6 wk of vitamin C supplementation (1000 mg/d) in elderly women (mean age: 72.8 y) resulted in no significant changes in leukocyte expression of genes encoding the proinflammatory markers IL-1, IL-6, and CRP or the anti-inflammatory marker IL-10 ( 94 ). However, a clear trend of decreasing IL-6 and increasing in IL-10 mRNA was observed ( 94 ). A 6-wk randomized controlled trial (RCT) of vitamin C (1000 mg/d) in patients aged 45 to 60 y with diagnosed type 2 diabetes and poor glycemic control reported increased phagocytosis and oxidative burst by granulocytes ( 95 ).…”
Section: Micronutrients Immunity and Infection With An Emphasis On Ol...mentioning
confidence: 99%